High-performance icephobic droplet rebound surface with nanoscale doubly reentrant structure. (April 2019) - Liao, Dong; He, Minghao; Qiu, Huihe
Graphical abstract: Highlights: The smallest doubly reentrant cavity was provided by improved fabrication methods. Extremely low surface tension liquids can stay Cassie state on this surface. The new surface outperforms traditional designs in room/freezing impacting tests. Analysis on impacting pressure and dynamic/static resistance force are conducted. Abstract: A bioinspired superomniphobic surface integrating doubly reentrant nanostructures with microcavities is proposed for simultaneously increasing static repellency and dynamic pressure resistance. Novel micro/nano fabrication techniques were developed for fabricating 15 μm doubly reentrant micro-cavities, which is the smallest in the world. Static and dynamic wetting experiments were conducted on pillared, doubly reentrant, cavity and the newly developed surfaces under different surface temperatures. It is found that the newly fabricated surface has the shortest contact time in comparison with other superhydrophobic surfaces, which depressed the ice nucleation on the surface below freezing temperature and, therefore, enhance the ability of icephobic. The experimental results show that the newly developed surface can not only successfully suspend the liquid with extremely low surface tension but also can repel droplets with an impact Weber number as high as 10 3 under a room temperature condition which is twice higher than previous research. Especially, even at −5 °C surface temperature, the newly developed surface can still repel droplets under Weber number of 335 while conventional cavity surface failed to repel droplets under the same Weber number at surface temperature −2 °C. The mechanism behind the excellent performance of the newly developed surface is analyzed utilizing "air spring effect", and micro wetting behavior of Laplace Breakthrough on nanostructures. Breakthrough pressure on the novel surface was three times larger than that of the cavity design. It is suggested that this kind nanostructured doubly reentrant cavity surface is promising which has potential applications in anti-icing and biofluid resistance.